Macronyssus ellipticus - Orlova, M. V.; Klimov, P. B.; Orlov, O. L.; Smirnov, D. G.; Zhigalin, A. V.; Budaeva, I. V.; Emelyanova, A. A.; Anisimov, N. V. (Zenodo, 2021)
Macronyssus ellipticus (Kolenati, 1856) Caris ellipticus Kolenati, 1856: 16. Liponyssus ellipticus .— Hirst, 1922: 795. Ichoronyssus mohrae Vitzthum, 1932: 32 (synonymy by Radovsky, 1966). Ichoronyssus ellipticus .— Pinchuk, 1970: 82. Macronyssus ellipticus .—Fonseca, 1941: 263; Radovsky, 1966: 94; 1967: 128; Beron, 1968: 159; Haitlinger, 1978: 707; Haitlinger & Ruprecht, 1985: 616; Baker & Beccaloni, 2006: 173; Scheffler, 2010; Radovsky, 2010: 56. Type locality: unknown. Type host: Myotis myotis (Kolenati, 1856). Material. F, 4 N1 ex Natterer’s bat Myotis nattereri , from Staritsa, 29 February 2020, leg. O.L. Orlov, A.A. Emelyanova; 9 N1 ex Myotis nattereri , N1 ex Myotis mystacinus , 3 N1 ex Myotis brandtii , from Samara, 25 November 2001, leg. D.G. Smirnov; N1 ex M . brandtii , M ex Plecotus auritus , 5 N1 ex M . daubentonii , 4 N1 ex M . dasycneme , from SNR “Samarskaya Luka”, 1-31 May 2005 leg. D.G. Smirnov. Distribution in Russian Federation: Leningrad Province (Stanyukovich, 1990a; Orlova et al ., 2015d), Tver Province (present paper), Samara Province (present paper), Northern Osetiya Republic (Stanyukovich, 1997), Sverdlovsk Province (Orlova, 2011), Chelyabinsk Province (Orlova & Orlov, 2013), Altai Region (Orlova et al ., 2017a), Primorskiy Region (Tiunov et al ., 2021), [Far East] (Stanyukovich, 1997), [Urals, Altai] (Orlova et al ., 2015d). Distribution outside Russian Federation: Europe (Radovsky, 1967), Central Asia (Stanyukovich, 1997). Hosts. Myotis myotis (Radovsky, 1967), M . blythii (Radovsky, 1967), M . brandtii (Orlova, 2011), M . dasycneme (Stanyukovich, 1990a), M . daubentonii (Stanyukovich, 1990a), M . nattereri (Stanyukovich, 1997; present paper), M . brandtii (Stanyukovich, 1990a), M . macrodactylus (present paper), M . mystacinus (Orlova & Orlov, 2013), Vespertilio murinus (Beron, 2014), Plecotus auritus (Orlova & Orlov, 2013), Murina hilgendorfi (as M . leucogaster — Stanyukovich, 1997), Rhinolophus ferrumequinum (Radovsky, 1967), Rh . hipposideros (Radovsky, 1967), Miniopterus schreibersi (Beron, 2014). : Published as part of Orlova, M. V., Klimov, P. B., Orlov, O. L., Smirnov, D. G., Zhigalin, A. V., Budaeva, I. V., Emelyanova, A. A. & Anisimov, N. V., 2021, A checklist of bat-associated macronyssid mites (Acari: Gamasina: Macronyssidae) of Russia, with new host and geographical records, pp. 537-564 in Zootaxa 4974 (3) on page 546, DOI: 10.11646/zootaxa.4974.3.4, http://zenodo.org/record/4778060 : {"references": ["Kolenati, F. A. (1856) Die Parasiten der Chiroptern. R. R. Erben, Brno, 51 pp.", "Hirst, S. (1922) On some new parasitic mites. Proceedings of the Zoological Society of London, 53, 769 - 802. [1921] https: // doi. org / 10.1111 / j. 1096 - 3642.1921. tb 03291. x", "Vitzthum, H. (1932) Neue parasitische Fledermausmilben aus Venezuela. Zeitschrift fur Parasitenkunde, 4, 1 - 47. https: // doi. org / 10.1007 / BF 02122048", "Radovsky, F. (1966) Revision of the macronyssid and laelapid mites of bats: outline of classification with descriptions of new genera and new type species. Journal of Medical Entomology, 3, 93 - 99. https: // doi. org / 10.1093 / jmedent / 3.1.93", "Pinchuk, L. M. (1970) [The mites of the genus Ichoronyssus (Gamasoidea: Dermanyssidae) of bats from the region between Prut and Dnester rivers]. Paraziti pozvonochnih zhivotnih, Kartea Moldoveniasca, 1970, 73 - 87. [in Russian]", "Radovsky, F. (1967) The Macronyssidae and Laelapidae (Acarina: Mesostigmata) parasitic on bats. University of California, Berkeley, California, 288 pp.", "Beron, P. (1968) Notes sur quelques Acariens des fam. Myobiidae, Spinturnicidae et Macronyssidae, parasites des chauvessouris en Bulgarie. Bulletin de l'Institut de Zoologie et Musee, 27, 51 - 53.", "Haitlinger, R. (1978) Pasozyty zewnetrzne nietoperzy Dolnego Slaska. IV. Macronyssidae, Dermanyssidae, Veigaiaidae. Wiadomosci Parazytologiczne, 24, 707 - 716.", "Baker, A. S. & Beccaloni, J. (2006) Macronyssus macroscutatus (Mesostigmata: Macronyssidae), a new mite species from bats of the genus Nyctalus (Chiroptera: Vespertilionidae) in England. Systematic & Applied Acarology, 11, 167 - 174. https: // doi. org / 10.11158 / saa. 11.2.4", "Scheffler, I. (2010) Ectoparasites of bats in hibernation places in Brandenburg. Markische Entomologische Nachrichten, 12, 119 - 132.", "Radovsky, F. (2010) Revision of Genera of the parasitic mite family Macronyssidae (Mesostigmata: Dermanyssoidea) of the world. Indira Publishing House, West Bloomfield, Michigan, 170 pp.", "Stanyukovich, M. K. (1990 a) [Gamasid and Argasidae mites of bats of Baltic states and Leningradskaya oblast]. Parazitologiya, 24, 193 - 199. [in Russian]", "Orlova, M. V., Stanyukovich, M. K. & Orlov, O. L. (2015 d) Gamasid mites (Mesostigmata: Gamasina) associated with bats (Chiroptera: Vespertilionidae, Rhinolophidae, Molossidae) of boreal Palaearctic zone (Russia and adjacent countries). Publishing House of Tomsk State University, Tomsk, 150 p\u0440.", "Stanyukovich, M. K. (1997) Keys to the gamasid mites (Acari: Parasitiformes, Mesostigmata, Macronyssoidea et Laelaptoidea) parasiting bats (Mammalia, Chiroptera) from Russia and adjacent countries. Rudolstadter Naturhistorische Schriften, 7, 13 - 46.", "Orlova, M. V. & Orlov, O. L. (2013) [New finds of ectoparasites in the caves of Southern Urals]. Vestnik Udmurtskogo universiteta. Seria Biologia. Nauki o Zemle, 3, 44 - 50. [in Russian]", "Orlova, M. V., Kazakov, D. V., Kravchenko, L. B. & Zhigalin, A. V. (2017 a) Ectoparasite fauna of the Siberian bat Myotis sibiricus (Chiroptera: Vespertilionidae) with a revision of previous data on ectoparasites from Brandt's bat Myotis brandtii s. l. and the whiskered bat M. mystacinus s. l. of the Eastern Palaearctic. Entomological Review, 97, 1166 - 1173. https: // doi. org / 10.1134 / S 0013873817080164", "Tiunov, M. P., Kruskop, S. V. & Orlova, M. V. (2021) [Bats of Far East and Their Ectoparasites]. Pero, Moscow, 190 pp. [in Russian]", "Beron, P. (2014) Acarorum Catalogus III: Opilioacarida, Holothyrida, Mesostigmata. Pensoft & National Museum of Natural History, Sofia, 286 pp."]}